Pengaruh Teknik Budidaya SRI (System of Rice Intensification) dan Legowo Terhadap Iklim Mikro dan Produktivitas Padi Ketan (Studi Kasus di Subak Sigaran) - I Putu Sanjaya; I Wayan Tika; S - Sumiyati (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2014)
This study was conducted to determine the effect of planting System of Rice Intensification (SRI) and legowo 6:1 row planting system of the microclimate and the rice plants productivity. This study was divided into 4 treatments with 3 replications, ie treatments conventional techniques, SRI method of planting, application of legowo 6:1 row planting system, and combination of SRI planting method and legowo 6:1 row planting system. The results showed the application of SRI planting method and legowo 6:1 row planting system not affecting the microclimate conditions, but affecting the productivity of riceplants. The results also showed that treatment K3 applying SRI methods combined with legowo 6:1 row planting system is the best treatment compared with other treatments.